2022
DOI: 10.3389/fspas.2022.1066480
|View full text |Cite
|
Sign up to set email alerts
|

sami2py—Overview and applications

Abstract: sami2py is a Python module that runs the SAMI2 (Sami2 is Another Model of the Ionosphere) ionospheric model, as well as load and archive the results. SAMI2 is a model developed by the Naval Research Laboratory to simulate the motions of plasma in a two-dimensional ionospheric environment along a dipole magnetic field. SAMI2 solves for the chemical and dynamical evolution of seven ion species in this environment (H+, He+, N+, O+, N2+, NO+, and O2+). The Python implementation allows for additional modifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…HWM14 is an improved version of older models such as HWM93 and HWM07 and provides a reliable reference for the validation of general circulation models (e.g., Drob et al, 2008Drob et al, , 2015Emmert et al, 2008;Tang et al, 2021). SAMI2 is a two-dimensional ionospheric model for the dynamical plasma and chemical evolution of seven ions (H + , He + , N + , O + , N 2 + , NO + , and O 2 + ) in the low-and mid-latitudes ionosphere over a range of altitudes 90-20,000 km (e.g., Huba et al, 2000;Klenzing et al, 2021Klenzing et al, , 2022. The ion and electron densities, ion velocities, and energy equations are treated as a system of advection/diffusion equations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HWM14 is an improved version of older models such as HWM93 and HWM07 and provides a reliable reference for the validation of general circulation models (e.g., Drob et al, 2008Drob et al, , 2015Emmert et al, 2008;Tang et al, 2021). SAMI2 is a two-dimensional ionospheric model for the dynamical plasma and chemical evolution of seven ions (H + , He + , N + , O + , N 2 + , NO + , and O 2 + ) in the low-and mid-latitudes ionosphere over a range of altitudes 90-20,000 km (e.g., Huba et al, 2000;Klenzing et al, 2021Klenzing et al, , 2022. The ion and electron densities, ion velocities, and energy equations are treated as a system of advection/diffusion equations.…”
Section: Methodsmentioning
confidence: 99%
“…The Kp and F107 indices can be obtained in OMNIweb (https://omniweb.gsfc.nasa.gov/form/dx1.html). The SAMI2 modeled values are generated using sami2py 0.2.5 (Klenzing et al, 2021(Klenzing et al, , 2022. The sami2py software is freely available at https://github.com/sami2py/sami2py.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…SAMI2 is a low latitude physics‐based ionospheric model developed at the Naval Research Laboratory (Huba et al., 2000; Klenzing et al., 2022). It models the ionosphere evolution in a meridional plane, with the neutral species specified by the MSIS model (Picone et al., 2002), and a variety of models as the input of the electric field and neutral winds.…”
Section: Methodsmentioning
confidence: 99%
“…This is an intriguing question, since the frequent occurrence of the irregularities observed in this region (Aa et al., 2020; Yizengaw et al., 2013) has challenged the conventional wisdom of the stabilizing effect of neutral winds. In this study, we first use the C/NOFS ion drift data and the observed peak height of ionospheric F2 region (hmF2) to constrain the SAMI2 model (Huba et al., 2000; Klenzing et al., 2022) and reconstruct the nighttime wind condition. Then the model outputs are used to compute the growth rate of GRT instability, the local time (LT) dependence of the irregularities is explained, and the effects of neutral winds are evaluated by controlling the wind input to the model.…”
Section: Introductionmentioning
confidence: 99%
“…For a given version of the software, the different applications can be rated at different levels. For example, the usage of the software in early phase research projects was rated at a level of AUL 7 (application prototype) as this is actively being used by researchers, while the usage of the software as a educational tool is rated as Phase 1 since the needs of a broader user base (i.e., students from a wider range of computational backgrounds) is still actively being identified (Klenzing et al, 2022). These new user requirements will inform the future versions and releases of the software.…”
Section: Software Developmentmentioning
confidence: 99%